2003
DOI: 10.1063/1.1539294
|View full text |Cite
|
Sign up to set email alerts
|

Soft magnetic properties of high-temperature nanocrystalline alloys: Permeability and magnetoimpedance

Abstract: Articles you may be interested inEffect of magnetic field annealing methods on soft magnetic properties for nanocrystalline (Fe0.5Co0.5)73.5Si13.5B9Nb3Cu1 alloy J. Appl. Phys. 117, 17B729 (2015) The technological applicability of FeCoNbBCu alloys is suggested in terms of measurements of room temperature magnetoimpedance and temperature dependence of magnetic permeability r . Results for the Fe 78-x Co x Nb 6 B 15 Cu 1 alloy series show that room temperature soft magnetic properties are enhanced in the lowest C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Although a high saturation magnetization was achieved in HITPERM alloys [6], as well as a wide temperature range of constant permeability [8], the coercivity at room temperature increases one or two orders of magnitude with respect to the Co-free alloys (from 1-10 A/m up to ~100 A/m [6,9]). Focusing on this problem, Suzuki et al recently proposed a small substitution of Ge for Fe as a more effective way to improve soft magnetic properties at high temperatures than the partial substitution of Co for Fe [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a high saturation magnetization was achieved in HITPERM alloys [6], as well as a wide temperature range of constant permeability [8], the coercivity at room temperature increases one or two orders of magnitude with respect to the Co-free alloys (from 1-10 A/m up to ~100 A/m [6,9]). Focusing on this problem, Suzuki et al recently proposed a small substitution of Ge for Fe as a more effective way to improve soft magnetic properties at high temperatures than the partial substitution of Co for Fe [10].…”
Section: Introductionmentioning
confidence: 98%
“…The maximum Co concentration studied in the alloys is 20 at. %, in order to search for a new showed that this parameter is seriously deteriorated for higher Co contents [6][7][8][9]. Although Ge is soluble in -Fe, the benefits of its addition to NANOPERM alloys would be due to its partition to the residual amorphous matrix [10], not producing a deleterious effect on the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although TCP values of this paper are not better than the previously reported, the larger values of make these alloys interesting for applications. In the case of 5 at.% Co alloy, at room temperature and 6 kHz, ϳ 4000 is four times larger than that of Fe 39 Co 39 Nb 6 B 15 Cu 1 alloy 7 …”
Section: E721-2mentioning
confidence: 84%
“…18͔͒, with ⌬T extended up to 900 K. The maximum permeability reported among these alloys was ϳ 1000. 7 For the two systems subject of the present paper, the optimum values of TCP are 0.10%/K and 0.04%/K for Co5 and Co20 alloys, respectively, in a temperature range from room temperature up to 915 K. For applications, a compromise between TCP and values should be found. Therefore, although TCP values of this paper are not better than the previously reported, the larger values of make these alloys interesting for applications.…”
Section: E721-2mentioning
confidence: 99%
See 1 more Smart Citation